2007
DOI: 10.1017/s1355617707070798
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of decision making in anorexia nervosa using the Iowa Gambling Task and skin conductance measurements

Abstract: The objective of this study is to determine (a) if decision making ability is impaired in patients with anorexia nervosa (AN) and in people with good recovery from AN and (b) whether any impairment in decision making is associated with alterations in skin conductance responses (SCR). Patients with AN (n = 29), healthy controls comparable in age and IQ (HC, n = 29), and women long term recovered from AN (n = 14), completed the Iowa Gambling Task (IGT) while their SCR were measured. AN patients performed poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
140
3
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(161 citation statements)
references
References 32 publications
13
140
3
2
Order By: Relevance
“…The most replicated ones are related to attention (Kingston et al, 1996;Lauer et al, 1999;Seed et al, 2002), working memory (Green et al, 1998;Kemps et al, 2006), cognitive flexibility (Steinglass et al, 2006;Tchanturia et al, 2004), SIP (Fowler et al, 2006;Gillberg et al, 2007;Kingston et al, 1996;Lauer et al, 1999;Seed et al, 2002;Tchanturia et al, 2004), and problem solving (Cavedini et al, 2004;Salvador et al, 2010;Tchanturia et al, 2007). It is yet to be clarified whether these impairments are caused by weight loss and BMI reduction or, conversely, if they may form the basis of the illness and be considered a determinant factor for AN to develop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most replicated ones are related to attention (Kingston et al, 1996;Lauer et al, 1999;Seed et al, 2002), working memory (Green et al, 1998;Kemps et al, 2006), cognitive flexibility (Steinglass et al, 2006;Tchanturia et al, 2004), SIP (Fowler et al, 2006;Gillberg et al, 2007;Kingston et al, 1996;Lauer et al, 1999;Seed et al, 2002;Tchanturia et al, 2004), and problem solving (Cavedini et al, 2004;Salvador et al, 2010;Tchanturia et al, 2007). It is yet to be clarified whether these impairments are caused by weight loss and BMI reduction or, conversely, if they may form the basis of the illness and be considered a determinant factor for AN to develop.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, after Halmi et al (2003) suggested a common pathway might be involved both in AN and obsessive compulsive disorder (OCD), investigations attempted to focus on the frontal impairment profiles by studying cognitive capabilities located in the frontal and prefrontal cerebral areas. Several investigations demonstrated impairments in attentional capabilities (Kingston et al, 1996;Lauer et al, 1999;Seed et al, 2002), mental flexibility (Steinglass, Walsh, & Stern, 2006;Tchanturia et al, 2004), speed of information processing (SIP; Fowler et al, 2006;Gillberg et al, 2007;Kingston et al, 1996;Lauer et al, 1999), working memory (Kemps, Tiggemann, Wade, BenTovim, & Breyer, 2006), and decision making (Cavedini et al, 2004;Tchanturia et al, 2007), while others failed to replicate these findings (Cavedini et al, 2004;Gillberg et al, 2007;Kemps et al, 2006;Kingston et al, 1996;Steinglass et al, 2006;Tchanturia et al, 2007). Nonetheless, an agreement appears to exist about the severity of impairments, given that all of the authors have reported that these impairments are subtle when compared with healthy control subjects.…”
Section: Cognitive Functioningmentioning
confidence: 99%
“…Another study that used the IGT to measure decision making in participants with eating disorders, though (anorexia in this case) concluded that this particular group demonstrated a deficient performance on the task in comparison with a control group and with a group of participants who had already had anorexia at another time in their lives. It has been noted that participants who have already had anorexia nervosa at some time in their past do not show results like this in the test (40). This result suggests that after an eating disorder is overcome, deficits in EF are no longer significant.…”
Section: Score Medium Without Bedmentioning
confidence: 87%
“…Hinson et al (2006) say that it is not possible to know how many different choices were actually being deliberated in this period, only that a particular choice was ultimately made. There are some newer studies which have examined the interval after the card selection and before feedback (Tchanturia et al, 2007). We decided to examine somatic markers in that interval too, because in our opinion it better reflects increasing arousal related to the anticipation of the outcome of the concrete decision made.…”
Section: Scr and Hr Measurementmentioning
confidence: 99%